1989
DOI: 10.1126/science.245.4921.962
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Coordination and Speciation Changes in a Silicate Liquid at High Pressures

Abstract: Coordination and local geometry around Si cations in silicate liquids are of primary importance in controlling the chemical and physical properties of magmas. Pressure-induced changes from fourfold to sixfold coordination of Si in silicate glass samples quenched from liquids has been detected with (29)Si magic-angle spinning nuclear magnetic resonance spectrometry. Samples of Na(2)Si(2)O(5) glass quenched from 8 gigapascals and 1500 degrees C contained about 1.5 percent octahedral Si, which was demonstrably pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
190
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(220 citation statements)
references
References 23 publications
28
190
2
Order By: Relevance
“…High-coordinated Si has been previously reported in high-pressure silicate glasses (Xue et al 1989(Xue et al , 1991Stebbins and Poe 1999;Allwardt et al 2004), and high-coordinated Al has been observed using various techniques in aluminosilicate glasses Yarger et al 1995;Li et al 1995;Poe et al 2001;Lee et al 2006;Allwardt et al 2005aAllwardt et al , 2005bKelsey et al 2009). However, in aluminosilicate glasses the Al apparently changes coordination more readily than does the Si and, to date, high-coordinated Si has not been directly observed in high-pressure aluminosilicate glasses (Yarger et al 1995;Allwardt et al 2007;Kelsey et al 2009), although it has been inferred from 17 O 3QMAS NMR (Lee 2004).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…High-coordinated Si has been previously reported in high-pressure silicate glasses (Xue et al 1989(Xue et al , 1991Stebbins and Poe 1999;Allwardt et al 2004), and high-coordinated Al has been observed using various techniques in aluminosilicate glasses Yarger et al 1995;Li et al 1995;Poe et al 2001;Lee et al 2006;Allwardt et al 2005aAllwardt et al , 2005bKelsey et al 2009). However, in aluminosilicate glasses the Al apparently changes coordination more readily than does the Si and, to date, high-coordinated Si has not been directly observed in high-pressure aluminosilicate glasses (Yarger et al 1995;Allwardt et al 2007;Kelsey et al 2009), although it has been inferred from 17 O 3QMAS NMR (Lee 2004).…”
mentioning
confidence: 93%
“…As sodium silicate glasses densify, V,VI Si forms and is most abundant in the Na 2 Si 4 O 9 composition (Xue et al 1989(Xue et al , 1991. It appears that these high-coordinated species are initially generated at the expense of non-bridging oxygen (NBO), but may involve bridging O atoms (BO) as well at higher pressures (Wolf et al 1990), as has also been reported for high-pressure potassium silicate glasses (Allwardt et al 2004).…”
mentioning
confidence: 99%
“…4,5,[13][14][15][16] Although all of the observed stable and metastable crystalline phases of silica consist of either IV Si or VI Si, there has been great interest in the possibility of forming phases in which silicon has fivefold coordination by oxygen ( V Si). This species has been predicted in theoretical studies of the effects of pressure and temperature on silicate melts and glasses [17][18][19][20][21][22][23][24][25][26][27] and inferred experimentally by 29 Si NMR and vibrational spectroscopy in alkali silicate liquids and glasses. 16,[28][29][30][31][32][33][34][35][36] Silicon has also been found in fivefold coordination with oxygen in a number of organosilicon compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This species has been predicted in theoretical studies of the effects of pressure and temperature on silicate melts and glasses [17][18][19][20][21][22][23][24][25][26][27] and inferred experimentally by 29 Si NMR and vibrational spectroscopy in alkali silicate liquids and glasses. 16,[28][29][30][31][32][33][34][35][36] Silicon has also been found in fivefold coordination with oxygen in a number of organosilicon compounds. 37,38 V Si has been proposed to play a role in the dissolution of silicates, [39][40][41] the increased diffusivity of liquid SiO 2 under pressure, 18 and viscous flow processes of other silicate melts.…”
Section: Introductionmentioning
confidence: 99%
“…In general the conclusion has been reached that either there is little or no coordination change, or it is unquenchable to room pressure: For example, for SiO2 glasses it is has been shown that an increase in pressure up to 30 kbar produces no changes of the Si-O bond-length of the network-forming tetrahedra but produces instead a decrease of the intertetrahedral angles (Seifert et al 1983;Davoli et al 1992). Highly sensitive NMR investigations have identified the presence of several percent of more highly coordinated Si from pressures much higher than those accessed in this work (Stebbins and McMillan 1989;Xue et al 1989). Only one report of a pressure induced coordination change of A1 exists to date, that of Ohtani et al (1985).…”
Section: Discussionmentioning
confidence: 97%